2017
DOI: 10.1371/journal.pone.0179647
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes mellitus and risk of type 2 diabetes 10 years after the index pregnancy in Sri Lankan women—A community based retrospective cohort study

Abstract: BackgroundWomen with a history of gestational diabetes mellitus (GDM) have an increased risk of type 2 diabetes mellitus (T2DM) later in life compared to women with no GDM. This study was aimed to determine the risk of developing T2DM 10 years after GDM in Sri Lankan women.MethodsA retrospective cohort study was conducted in the Colombo district, Sri Lanka. 7205 women who delivered a child in 2005 were identified through Public Health Midwives in the field. Women with antenatal records were interviewed and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 29 publications
10
86
3
Order By: Relevance
“…This result seems to be less compared to previously published studies and similar to only one other study from Sweden where diabetes prevalence was 3.4% among women 3-4 years after childbirth (21). The majority of other studies report higher prevalence rates, ranging from 14% (9) or 20% (13) by 11 or 9 years postpartum and up to 33.3% among women investigated 5-10 years postpartum (15). We believe a longer period of follow up in the latter studies might be the cause of higher diabetes prevalence compared to the one observed in our study.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…This result seems to be less compared to previously published studies and similar to only one other study from Sweden where diabetes prevalence was 3.4% among women 3-4 years after childbirth (21). The majority of other studies report higher prevalence rates, ranging from 14% (9) or 20% (13) by 11 or 9 years postpartum and up to 33.3% among women investigated 5-10 years postpartum (15). We believe a longer period of follow up in the latter studies might be the cause of higher diabetes prevalence compared to the one observed in our study.…”
Section: Discussioncontrasting
confidence: 58%
“…On the other hand, women burdened with GD during pregnancy are at risk of developing diabetes later in life. Studies have reported that women with GD during pregnancy have a seven to twelve times (8)(9)(10) higher risk of developing type 2 diabetes compared with women who are normoglycaemic during pregnancy and, according to a systemic literature review by Kim et al (11), the occurrence rate is highest in the first 5 years after pregnancy. This systemic review also revealed a wide range of cumulative incidence of diabetes ranging from 2.6% to over 70%, which is presumably due to different follow-up periods among studies expanding from 6 weeks to 28 years postpartum.…”
Section: Introductionmentioning
confidence: 99%
“…Common examples include pre-eclampsia (discussed above) and GDM, which increases the risk of future type 2 diabetes, and can be further influenced by ethnicity. 18,19 Combined NCDs are the leading cause of death in women worldwide, accounting for 65% of all deaths. 20 Estimates suggest that, in 2030, a two-thirds reduction in maternal and child deaths, and a one-third reduction in NCD mortality would mean 210 000 fewer maternal deaths and 690 000 fewer NCD deaths in women and girls aged 5-49 years, and 2.4 million fewer NCD deaths in women aged 50-69 years.…”
Section: Merging the Maternal Health And Ncds Agendasmentioning
confidence: 99%
“…A retrospective cohort study was conducted in eight Medical Officer of Health (MOH) areas in Colombo district, Sri Lanka from March 2015 to October 2016 to assess the long term outcomes of HIP on the mother and the offspring. We have previously published the risk of type 2 diabetes in the mothers 10 years after gestational diabetes [39].…”
Section: Methodsmentioning
confidence: 99%